Évaluer la qualité des relations éducatives pour favoriser le bien-être : une utilisation possible du Classroom Assessment Scoring System (CLASS) ? - Marlène Martin; Pascale Haag (Éducation et Socialisation, 2023)
The quality of relationships is recognized as an essential determinant of students' well-being at school. To try to understand it, different methods have been proposed, including the Classroom Assessment Scoring System (CLASS), a tool for observing and evaluating the quality of interactions in an educational context. Developed by the team of Pianta, La Paro and Hamre in the United States since 2008 and widely used in the world, it is still little known in France. This article describes this tool by focusing on the dimensions related to the quality of relationships between students and teachers. It then presents a review of the international literature exploring its use to assess relationships and for training purposes. Taking into account the criticisms about the tool, the relevance and possibility of its use to evaluate and train in the quality of the educational relationship in the French context are discussed.well-being, quality of relations, Classroom Assessment Scoring System, observation, assessment, teachers’ training.